PELATIHAN PENERAPAN PRINSIP KERJASAMA DAN KESOPANAN DI SMA - Mansyur, Firman Alamsyah; Arsad; Muammar; Yaumi; Muhtar; Widianto; Alan Zulhijah (Unmuh Babel Press, 2021)
The ability to cooperate and politely communicate with other parties is very important in this era of the industrial revolution. On the other hand, students still do not understand the importance of cooperation and politeness for their success in the future. Therefore, this Community Service Activity is caused by two things, namely: a) the low ability of students to cooperate in communicating, and b) the low knowledge of students regarding politeness in communicating with teachers, peers, and younger people. Therefore, this study aims to provide training related to the principles of cooperation and politeness to students in communicating. The method used in this research is the lecture method, question and answer, and group discussion. The results of this study revealed that high school students were very happy to participate in this training because they could know the types of cooperative principles that they could apply in communicating. In addition, they become more understanding about the types of politeness in building communication with teachers, students of the same age, and younger people. The implication of this study emphasizes that the application of the principles of cooperation and courtesy is very appropriate to be taught in schools, both by school principals and teachers to their students.